The Effect of Settling Agent on Bromelain Enzyme Isolation from Pineapple Core - Salahudin, Farid (Balai Riset dan Standardisasi Industri Pontianak, 2011)
Pineapple is one of the most potential agricultural commodities from West Kalimantan. Pineapple is the promising source of protease enzyme which is called bromelaine enzyme. The aim of this research was to obtain the best technology of bromelain enzyme isolation. The variable in this research were the concentration of ammonium sulphate and ethanol which their degrees were 20, 40, 60 and 80%. Enzyme isolate was tested the activity of protease enzyme with the modification of lowry method. The technology of enzyme isolation with ammonium sulfat 80% is can produced the best of enzyme isolate with 0,61% rendement and the enzyme activity is 12.500 U/ml.